Analisis Kontrastif Partikel Bahasa Jepang dan Bahasa Jawa - Ittaqy Tafuzy Nurul Aini; Elizabeth Ika Hesti Aprilia Nindia Rini (Vocational College of Diponegoro University, 2023)
This research was conducted to explain the structure and meaning of case particles in Japanese and prepositional particles in Javanese, also to explain the similarities and differences between particles both in two languages. The data of particle in Japanese was obtained from websites, and particle in Javanese was obtained from magazine. The first step of this research was to collecting data using catat method. Then, data were analyzed using descriptive and contrastive analysis methods. The results were presented using an informal method, which explained in words. Case particles in Japanese has the same function and meaning as prepositional particle in Javanese. In terms of structure, case particles and prepositional particles both must attached to nouns, so that could be understand their meaning. While the differences are case particle placed behind the noun and prepositional particle placed in front of the noun.